STUDENTS’ PERCEPTIONS OF THE USING CHATGPT TO ENHANCE WRITING SKILLS AT MAN 3 BONE - Fadhil Afnur; Amirullah Amirullah; Miftah Fauzan (State University of Makassar, 2026)
This study investigates students’ perceptions of using ChatGPT as a learning tool to enhance English writing skills at MAN 3 Bone. Writing is considered a complex language skill that requires mastery of grammar, vocabulary, and sentence structure; however, many students still encounter difficulties in these areas. To address this issue, ChatGPT was introduced as an AI-assisted writing tool to support students during the writing process. This research utilized a mixed-methods design with a sequential explanatory strategy. Quantitative data were obtained from pre-tests and post-tests to evaluate students’ progress in writing, whereas qualitative data were collected through questionnaires and interviews to understand students’ perceptions and experiences. The study involved 20 participants selected using purposive sampling. The findings showed a notable improvement in students’ writing abilities after the use of ChatGPT, especially in grammatical accuracy, vocabulary expansion, and sentence construction. Additionally, students reported positive perceptions of ChatGPT., highlighting its usefulness in providing instant feedback, generating ideas, and increasing confidence in writing. Nevertheless, several students also emphasized the importance of teacher guidance to avoid overreliance on AI tools. In conclusion, the study determines that ChatGPT can function as an effective supporting tool for teaching English writing when it is applied appropriately and with proper guidance.Keywords: ChatGPT, students’ perceptions, writing skills, English language learning, artificial intelligence.